The impact of spousal retirement on health—an empirical analysis based on CFPS - Chen, Ping; Liang, Han; Zhou, Yufei; Zhu, Guodong; Peng, Yu; Yao, Jiayi (Frontiers in Medicine, 2025)
IntroductionHealth impacts associated with spousal retirement vary significantly across countries and datasets, underscoring the need to examine this relationship within the Chinese context. This study aims to explore how spousal retirement affects individual health in China.MethodsUtilizing data from the China Family Panel Studies (CFPS) for the years 2014, 2016, 2018, and 2020, this research applies a fuzzy regression discontinuity approach to assess the effects of spousal retirement on health outcomes.ResultsFindings indicate that a wife’s retirement positively impacts her husband’s mental health but negatively affects his physical health. Conversely, a husband’s retirement improves his wife’s self-rated health. Further analysis reveals that a husband’s retirement significantly enhances his wife’s marital satisfaction, contributing to longer sleep durations and, subsequently, better self-rated health.DiscussionThis study highlights the nuanced effects of spousal retirement on individual health, with implications for understanding the marital and health dynamics within aging populations in China.